The Fostering Religious Devotion in Arabic Military Students through Language Proficiency Development - Nurmala, Mia; Huda, MIftahul; Faqih, Ahmad (Al-Fusha : Arabic Language Education Journal, 2024)
Learning Arabic in this modern era has been carried out in military educational institutions. Religious values must be distinct from learning Arabic. This differs from another foreign language teaching which is professionally oriented and practical only. This study aims to simultaneously reveal the acquisition of proficiency in Arabic and increased religiosity. In this study, a phenomenological analysis was used by focusing on the process of teaching religious values to military students. The sampling technique uses purposive sampling. Data has been collected through observation, interviews and documentation at Pusdik Pengmilum. Respondents in this study consisted of military teachers, military students and academic units. The research results show that all language skills are obtained through learning. To strengthen the religious values of life and development in learning Arabic. Learning activities with the tri system of military education archetypes are very influential. This can be seen from the supervision of the education unit, which collaborates with gumil (military teacher) in acquiring skills and increasing religiosity.